Hydrological Drainage Effects on Microbial Dynamics in Badas Peatland: Fungal Decline, Bacterial Dominance, and Reduced Microbial Biomass Carbon - Sahat, Muhammad Hadi; Sukri, Rahayu Sukmaria; Jaafar, Salwana; Shivanand, Pooja; Gödeke, Stefan (ASEAN Journal for Science and Engineering in Materials, 2026)
Peatlands are globally important ecosystems for carbon storage and climate regulation, yet hydrological drainage for agriculture and infrastructure has disrupted their ecological balance. This study examined the effects of drainage on soil microbial communities and microbial biomass carbon (MBC) in Badas Peatland, Brunei Darussalam. Soil samples were collected along two transects (Jalan Badas Middle and North) and analyzed using microBIOMETER® and plate count methods. Results revealed that fungal abundance and MBC increased with distance from the drainage canal, whereas bacterial and actinomycete counts decreased. The fungal-to-bacterial ratio showed a strong positive correlation with MBC, indicating that drainage adversely affects fungal populations and soil carbon retention. These findings highlight that fungi are more sensitive to drainage-induced stress than bacteria, reducing the peatland’s capacity for carbon sequestration. The study emphasizes the need for sustainable water management strategies to preserve soil microbiology and mitigate carbon loss from tropical peatlands.